Variation in GUS activity in vegetatively propagated Hevea brasiliensis transgenic plants - Lardet L; Benistan E; Dessailly F; Leclercq J; Martin F; Montoro P; Oliver G (Plant Cell Reports, 2011)
Hevea brasiliensis transgenic plants are regenerated from transgenic callus lines by somatic embryogenesis. Somatic embryogenesis is not yet available for commercial propagation of Hevea clones, which requires conventional grafting of buds on rootstock seedlings (buddings). The stability of transgene expression in budded plants is therefore necessary for further development of genetic engineering in rubber trees. Transgene expression was assessed by fluorimetric beta-glucuronidase (GUS) activity in fully developed leaves of in vitro plants from transgenic lines and their sub-lines obtained by budding. A large variation in GUS activity was found in self-rooted in vitro plants of five transgenic lines, and the absence of activity in one line suggested transgene silencing. Beyond confirming transmissibility of the reporter gene by budding and long-term expression, a quantification of GUS acitivty revealed that greater variability existed in budded plants compared to self-rooted mother in vitro plants for three transgenic lines. Although somatic embryogenesis provided more stable GUS activity, budding remained an efficient way of propagating transgenic plants but transgene expression in budded plants should be verified for functional analysis and further development.
Keywords: Beta-glucuronidase; Gene silencing; Genetic transformation; Grafting; Rubber tree; Transgene